Implementation of Pakem by Teachers as an Effort to Grow Self-Confidence in Students in Outlying Areas - Eki Yanto Neonisa; Harun Y. Natonis (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study examines the contribution of the PAKEM (Participatory, Active, Creative, and Fun) learning model in fostering students' self-confidence in outlying areas, especially Hoi Village, Oenino District, South Central Timor Regency. The background of the study is the low self-confidence of students due to minimal parental support, social pressure, and geographical and economic challenges that affect the quality of learning. This study aims to identify learning strategies used by teachers to build students' self-confidence and improve their learning achievement. The method used is a qualitative approach through literature studies and interviews with three informants: two elementary school teachers who actively teach and open free tutoring, and one local resident as a direct observer. The results of the study indicate that the implementation of the PAKEM model has a significant impact on increasing students' self-confidence through active, contextual, and fun learning activities. Teachers who are pedagogically sensitive are able to create an inclusive and supportive learning space, so that students feel valued and dare to express themselves. Despite obstacles such as time constraints, variations in student character, and a less than ideal teacher-student ratio, the PAKEM model still provides positive results in building learning motivation and restoring students' self-image. In conclusion, PAKEM is not just a learning method, but a transformative approach that is able to overcome students' psychological barriers and create a strong foundation of self-confidence to support children's academic success and character.